World War II and the Growth of the U.S. Federal Government - Hugh Rockoff (Rutgers University, Department of Economics, 1998)
It is frequently claimed that World War II contributed to the growth of big government in the United States. One theory is that agencies that were given additional resources or authority during the war were able to retain them after the war because the agencies and their supporters were able to take advantage of inefficiency and inertia in the political process. The public, moreover, it is said, had gotten use to higher taxes during the war, so it was not necessary for the government to lower taxes all the way to their prewar level. This is the famous 'ratchet' hypothesis. In this paper, however, I argue that there is little evidence for this phenomenon. On the other hand, I argue that the perception that government spending and control of the economy had proved successful during the war contributed to the ongoing shift in public attitudes in favor of big government.
Keywords: N42; 330; war